Delay in the diagnosis of dementia in urban India: Role of dementia subtype and age at onset. (16th November 2022) - Ellajosyula, Ratnavalli; Narayanan, Jwala; Hegde, Soumya; Kamath, Vikram; Murgod, Uday; Easwaran, Vandhana; Seetharam, Raghavendra; Srinivasan, Murali; Watson, Peter
Abstract: Background: Early diagnosis of dementia is crucial for timely intervention. However, frequently, there is a substantial delay in diagnosis. Therefore, it is essential to recognise and address the barriers to early diagnosis. These have not been systematically studied in India. We at a specialist memory clinic in India investigated the time from symptom onset to diagnosis of dementia and factors contributing to the delay. Methods: In this cross‐sectional study, consecutive patients with dementia ( n = 855) seen at a private hospital underwent a standard clinical assessment and investigations. The primary outcome variable was time from symptom onset to diagnosis (TTD). The association of age, education, gender, dementia subtype, and age of onset on TTD were examined using a univariate analysis of covariance. Results: The median TTD was 24 months; 43% were diagnosed after 24 months. There was a significant association between TTD and age at onset (young onset—median 36 months vs. late onset—24 months) and dementia subtype. Patients with vascular dementia were diagnosed significantly earlier as compared to patients with Alzheimer's disease (AD) and frontotemporal dementia (FTD) [median 18, 24, and 30 months, respectively]. There was no effect of gender or education on the TTD. Conclusion: About 40% of patients with dementia were diagnosed more than 2 years after symptom onset, particularly young onset dementias and FTD. Our study findings highlight the gaps in diagnosing patients with dementia in urban India and have significant implications for developing and implementing multifaceted interventions to improve the early diagnosis of dementia. Key points: Dementia is expected to be a major public health problem in India. There is very little information regarding the factors associated with delay in diagnosis of dementia in India. Our findings suggest that there is a delay in diagnosis of dementia in urban India which is more significant for young onset dementia and certain dementia subtypes like Alzheimer's disease and frontotemporal dementia. There is an urgent need to develop and implement interventions in India, firstly to educate the public and raise awareness of dementia, and secondly to train general physicians in recognising dementia symptoms and making an early diagnosis.